Impulsive differential equations by using the Euler method - Amir Hamzah1, Nor Shamsidah; Mamat, Mustafa; Kavikumar, J.; Lee, Siaw Chong; Ahmad, Noor’ani (-, 2010)
The theory of impulsive differential equations is emerging as an important area of investigation since such equations appear to represent a natural framework for mathematical modeling of several real phenomena. There have been intensive studies on the qualitative behavior of solutions of the impulsive differential equations. However, many impulsive differential equations cannot be solved analytically or their solving is complicated. In this paper, we represent the algorithm which follows the theory of impulsive differential equations to solve the impulsive differential equations by using the Euler methods. It is clearly shown the impulsive operators k I that acts at the moments k t influence the error. Finally, the better convergence result of the numerical solution is given by solving the numerical examples.